Internationalisation of small-medium size enterprises - Wyer, Peter; Mohd Shariff, Mohd Noor; Othman, Mohammad Azmi (1996)
In recent years Malaysia has demonstrated a remarkable and impressive growth record which is the envy of many other countries. A concerted effort to sustain this pace of development and to achieve fully industrialised nation status by 2020 is currently undenvay, with the contribution of small-medium sized enterprises (SMl's) seen as a critical and integral pan of this industrial thrust. The potential role of SMI's is emphasised in areas such as job creation, rural development, support infrastructure for large organisations and the earning of revenues from exporting activity.